Pengaruh Aplikasi Quizizz Sebagai Media Pembelajaran terhadap Keaktifan dan Prestasi belajar Siswa pada Pelajaran Kewirausahaan Kelas XII SMK N 8 Surakarta - Wahyudi Taufan Santoso; Rita Dwi Nawanti; Shodiq Purnomo; Masduki (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research is an experimental research motivated by the low learning achievement of students in entrepreneurship subjects in class XII SMK N 8 Surakarta. This study aims to determine whether or not there is an influence of the use of quizizz learning media on the learning achievement of grade XII students in entrepreneurship subjects of SMK N 8 Surakarta. The variables of this study consist of two, namely independent variables include quizizz learning media and dependent variables include student learning achievement. The research method used in this study is quantitative research with the type of experimental research using the Pretest-Posttest Control Group Design research design, with pre-test, treatment, and post test stages. The population in this study was all 34 students of grade XII SK 3 SMK N 8 Surakarta. The sample of this study was class XII SK 3 SMK N 8 Surakarta as an experimental group with a total of 34 students. The data collection techniques used are questionnaires, observation sheets, and documentation. Data analysis techniques used by testing hypotheses using t-tests with independent sample t-test types. The results of this study show that learning achievement after the use of quizizz learning media can be categorized as high. The conclusion of this study is that quizizz learning media has an influence on the learning achievement of students in class XII entrepreneurship subjects of SMK N 8 Surakarta.